Plantas promisorias de uso alimenticio del Darién, Caribe colombiano (2014)
ABSTRACT: This article analyzes the knowledge, uses and practices of 21 promisisng species for nutrition use, reported in successional forests, kitchen gardens, borders and yards in the town of San Francisco de Asís, Acandí, Chocó. This Project is the result of live months of fledwork using ethnobotanical methods followed by a systemic analysis that inquired about socioecological aspects of the edible species through ethnographic methods. The nutritional contribution of these species to food security was validated by means of standard bromatologic techniques. Many of them are in risk of disappearing form local cuisine and from the agroecosystems, due to deforestation processes, livestock, the introduction of industrially-processed food and the transformation from a self-sufficient small scale economy into an economy linked to the traffic or illegal drugs. Agroecology labels species such as the chupamelon, the cacaona, the oreja de Judas, and the papocho as local innocuous foods.